PENGARUH MEDIA DIGITAL ASSEMBLR EDU DALAM PEMBELAJARAN GEOGRAFI TERHADAP MOTIVASI BELAJAR SISWA KELAS XI SMA NEGERI UNGGULAN SUKMA NIAS: Penelitian Skripsi - Laowo, Priska Jernih Ventari; Prof. Dr. Dedi Hermon,MP (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role and impact of using the digital media Assemblr Edu in Geography learning on the learning motivation of eleventh-grade students at SMA Negeri Unggulan Sukma Nias. The research background arises from the low level of student motivation in Geography, which is characterized by passive participation, lack of interest in asking questions, and low activeness during the learning process. The research method employed is a quantitative approach with a quasi-experimental design involving two classes: an experimental class and a control class. The sampling technique used was total sampling, with all 64 students of grade XI Social Sciences serving as the research sample. The results show that the use of Assemblr Edu has a positive and significant effect on students’ learning motivation. This is evident from the significant differences between the two groups, with the mean score of the experimental class being much higher than that of the control class. However, the standard deviation values between the groups did not show a substantial difference. The t-test results also revealed a striking difference, with the experimental class obtaining a t-value of 23.314, compared to only 5.431 for the control class. Students in the experimental class demonstrated greater improvement in motivation, particularly in terms of attention, activeness, and self-confidence during the learning process. Therefore, the implementation of Assemblr Edu as a learning medium in Geography effectively enhances students’ learning motivation.